Análise exergoeconômica avançada de um sistema de cogeração otimizado - Almeida, Bruno Seixas Gomes de (2018)
The advanced exergoeconomics analysis has been used frequently in numerous recent studies to analyze thermal systems in general. In addition to the quantification of exergy destruction, destruction costs and investiments, the advanced analysis allows the fragmentation of these terms in avoidable, unavoidable, endogenous and exogenous parts. In this context, the present work aims to compare the results of the advanced economic analysis in different operating conditions of an optimized cogeneration system and to evaluate the differences between the advanced and conventional exergoeconomics analyses. To do so, three conditions are analyzed: system operating with minimum cost, system operating with maximum exergetic efficiency and system operating in an arbitrary condition. In order to obtain the lowest cost and highest efficiency conditions, optimization routines based on hybrid methods were used. There was a significant difference between the results of the advanced exergoeconomic analysis in each operating condition. In addition, it was noted that the advanced exergoeconomic analysis would lead to a different ranking of the equipment than the conventional one, for the improvement of the system. Based on the results, it is proposed the development of an optimization algorithm associated with the advanced exergoeconomic analysis to facilitate the path to the optimal condition.